Different types of out-of-home activities and well-being amongst urban residing old persons with mobility impediments. Issue 1 (March 2015) - Siren, Anu; Hjorthol, Randi; Levin, Lena
Abstract Independent mobility has been proposed to be a precondition for leading an independent, non-institutionalized life. Supporting independent mobility for the growing senior segment thus has societal importance. The question of how to maintain well-being through mobility in older age is, however, a complex one. The present study explicates this by focusing on how utilitarian and discretionary activities—representing different types out-of-home activities—contribute to well-being, using data from individual interviews with persons aged 80–95, living in Copenhagen, Denmark. We structured the material by the two activity types and found both to contribute to participants׳ well-being by representing different sides of 'being'. Utilitarian activities were important in maintaining independence and fulfilling basic needs, while discretionary activities were important for the individual existing in relation to the surroundings. Mobility-related well-being appears constructed both through independent separateness and through sense of community. This finding implies that supporting mobility in the sense of mere fulfilment of basic needs may not be enough.